2012
DOI: 10.1097/pcc.0b013e31825b582e
|View full text |Cite
|
Sign up to set email alerts
|

Activated partial thromboplastin time is a better trending tool in pediatric extracorporeal membrane oxygenation

Abstract: The activated clotting time is not an accurate monitoring tool for heparin management in pediatricextracorporeal membrane oxygenation. The point-of-care activated partial thromboplastin time correlates well with the clinical laboratory activated partial thromboplastin time but cannot be substituted for the clinical laboratory activated partial thromboplastin time values. Management of pediatric extracorporeal membrane oxygenation patients with the clinical laboratory activated partial thromboplastin time reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 29 publications
2
56
1
Order By: Relevance
“…However, the amounts of silica and phospholipids and the lack of other exogenous factors make the aPTT reagents a milder pro-coagulant and particularly useful for low-dose heparin monitoring. Recently, the aPTT has begun to find favor amongst clinicians for monitoring heparin therapy on ECMO because it has a better correlation to the heparin doses in adults [124][125][126][127], and is now typically measured on the modern ECMO patient [31]. The trend in lower heparin dosing and use of the aPTT have been shown to reduce patient bleeding events, and thereby decrease mortality [126].…”
Section: Activated Partial Thromboplastin Time (Aptt)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the amounts of silica and phospholipids and the lack of other exogenous factors make the aPTT reagents a milder pro-coagulant and particularly useful for low-dose heparin monitoring. Recently, the aPTT has begun to find favor amongst clinicians for monitoring heparin therapy on ECMO because it has a better correlation to the heparin doses in adults [124][125][126][127], and is now typically measured on the modern ECMO patient [31]. The trend in lower heparin dosing and use of the aPTT have been shown to reduce patient bleeding events, and thereby decrease mortality [126].…”
Section: Activated Partial Thromboplastin Time (Aptt)mentioning
confidence: 99%
“…Recently, the aPTT has begun to find favor amongst clinicians for monitoring heparin therapy on ECMO because it has a better correlation to the heparin doses in adults [124][125][126][127], and is now typically measured on the modern ECMO patient [31]. The trend in lower heparin dosing and use of the aPTT have been shown to reduce patient bleeding events, and thereby decrease mortality [126]. aPTT goals for most patients are 1.5-2.5 times age-normal values., which is important for the neonatal patient who will have prolonged aPTT times due to the nature of the development of their coagulation system [64,75].…”
Section: Activated Partial Thromboplastin Time (Aptt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific blood products are transfused if antithrombin activity is <70%, hemoglobin is <10 g/dL, fibrinogen is <150 mg/dL, platelet count is <45,000 cell/mm 3 (<80,000 cell/mm 3 in case of recent surgery) or prothrombin time ratio is >1.5. We rely on aPTT rather than activated clotting time (ACT) because it possibly better reflects heparin dosage (8) and anti-factor Xa activity (the gold standard for monitoring the anticoagulant effect of heparin) (6) during VV-ECMO. One single-center retrospective study reported fewer, potentially lethal, bleeding complications in pediatric patients receiving ECMO when heparin infusion was guided by aPTT compared to ACT (8).…”
Section: Hemostatic Changes During Vv-ecmomentioning
confidence: 99%
“…Using a similar target in subjects with hardly predictable concomitant changes in hemostasis could result in unacceptably frequent bleeding. The correlation between aPTT and heparin dosage or anti-factor Xa activity, although significant, is weak (6,8). aPTT does not provide any insight on other critical variables such as factor XIII activity and platelet count and function.…”
Section: Hemostatic Changes During Vv-ecmomentioning
confidence: 99%